Multifunctional Cu2+‐montmorillonite/epoxy resin nanocomposites with antibacterial activity. Issue 16 (20th April 2017) - Bartolozzi, Alessandra; Bertani, Roberta; Burigo, Elisa; Fabrizi, Alberto; Panozzo, Francesco; Quaresimin, Marino; Simionato, Fabio; Sgarbossa, Paolo; Tamburini, Sergio; Zappalorto, Michele; Zorzi, Federico
ABSTRACT: Multifunctional nanocomposites can be achieved by addition of modified layered nanoclays to impart to the final materials a designed set of properties. The easy reproducible preparation of copper modified montmorillonite has been reported here together with its spectroscopic characterization, including 29 Si NMR in the solid state. Epoxy‐nanocomposites and glass fiber reinforced laminates containing 1% wt and 3% wt of Cu 2+ ‐MMT have been prepared and characterized. Thermal and mechanical properties have been evaluated. The experiments carried out to evaluate the antibacterial activity showed that the epoxy‐resin nanocomposites with 3% wt of Cu 2+ ‐MMT exhibited an inhibition action higher than 96% against Escherichia coli and Staphylococcus aureus . © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44733. Abstract :